Сytogenetic effects in the bone marrow of rats with long-term ingestion of 131I - О. A. Sova (Ядерна фізика та енергетика)
Cytogenetic effects in the rats bone marrow after long-term ingestion of 131І were studied. Significant increase of chromosomal aberrations by dicentric aberrations with and without fragments, acentric fragments, atypical chromosomes and polyploidies was found. Chromatid-type aberrations in exposed animals were present at the same level as in the control group.